Pengembangan Media Pembelajaran Fisika Berbasis Model Educational Games Guna Meningkatkan Minat Belajar Melalui Rolling Box (Ro-Box) Bagi Peserta Didik Kelas X SMA N 2 Semarang - Ramadhani, Pawitrasari Mahestyas; Sugianto, Sugianto (UPEJ Unnes Physics Education Journal, 2020)
This research aims to: produce a physics-based learning media educational games form Rolling Box (Ro-Box) and knowing the increase in interest in learning physics of class X SMA students related to use Rolling Box (Ro-Box) as a medium for learning physics. This research is a research development (R&D) with a 4-D model (Define, Design, Develop, Disseminate). The subjects of this study consisted of 14 students of class X MIPA 8 and 28 students of class X MIPA 9 in SMA N 2 Semarang. Validation data for lecturers and physics teachers were obtained through a questionnaire. Student response data were obtained through a response questionnaire. Data to increase students' interest in learning were obtained through a questionnaire. The data analysis techniques used in this study were qualitative and quantitative. Qualitative data analysis techniques are used to analyze input from both validators and students. Quantitative data analysis techniques are used to analyze the validator's assessment, the results of student response questionnaires, increase interest in learning, and increase student learning outcomes. The results of this study are: based learning media educational games form Rolling Box (Ro-Box) can be applied in learning physics and an increase in students' interest in learning of achievement of 5.9%, including in the good category.